👤

[tex] \frac{x-14}{2000} + \frac{x-4}{2010} = \frac{x-2000}{14} + \frac{x-2010}{4} [/tex]

Răspuns :

[tex]\dfrac{x-14}{2000}+\dfrac{x-4}{2010} = \dfrac{x-2000}{14}+\dfrac{x-2010}{4}\Big|\cdot 2000\cdot 2010\cdot 14\cdot 4 \\ \\ 2010\cdot 14\cdot 4\cdot(x-14)+2000\cdot 14\cdot 4\cdot(x-4) = \\ =2000\cdot 2010\cdot 4\cdot (x-2000)+2000\cdot 2010\cdot 14\cdot(x-2010) \\ \\ x\cdot (2010\cdot 14\cdot 4+2000\cdot 14\cdot 4) - 2000\cdot 14^2\cdot 4-2000\cdot 14\cdot 4^2 = \\ =x\cdot (2000\cdot 2010\cdot 4+2000\cdot 2010\cdot 14)-2000^2\cdot 2010\cdot 4-\\-2000\cdot 2010^2\cdot 14 \\ [/tex]

[tex] x\cdot (2010\cdot 14\cdot 4+2000\cdot 14\cdot 4) - x\cdot (2000\cdot 2010\cdot 4+2000\cdot 2010\cdot 14) = \\ =2000\cdot 14^2\cdot 4+2000\cdot 14\cdot 4^2 -2000^2\cdot 2010\cdot 4-2000\cdot 2010^2\cdot 14 \\ \\ x\cdot (2010\cdot 14\cdot 4+2000\cdot 14\cdot 4-2000\cdot 2010\cdot 4-2000\cdot 2010\cdot 14) = \\ =2000\cdot 14^2\cdot 4+2000\cdot 14\cdot 4^2 -2000^2\cdot 2010\cdot 4-2000\cdot 2010^2\cdot 14 \\ \\[/tex]

[tex] x = \dfrac{2010\cdot 14\cdot 4+2000\cdot 14\cdot 4-2000\cdot 2010\cdot 4-2000\cdot 2010\cdot 14}{2000\cdot 14^2\cdot 4+2000\cdot 14\cdot 4^2 -2000^2\cdot 2010\cdot 4-2000\cdot 2010^2\cdot 14 }[/tex]
Vezi imaginea RAYZEN